Mekanisme Escape dan Respon Imun innate terhadap Candida albicans - Putu Oky ari Tania (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Candidiasis is an infection caused by fungal Candida albicans. The incidence of candidiasis is pretty high in Indonesia. Candida albicans develop their pathogenicity by several ways so that it can invade and escape from the immune system. The host’s immune system must always be vigilant to recognized antigen through various receptors, activation of the transduction pathway and activation of various immune cells. But as organisms that struggle to survive, Candida also develops mechanisms to escape the immune response. There are so many articles have written the immune response against candidiasis, this review aims to understand more and updating information about the biological processes of pathogenicity of fungi and the mechanism of Candida albicans in escaping immune responses, the role of each innate molecule and immune cell, and clinical aspect to Candida albicans infections. We already facing the big challenges against therapy of fungal infection, so by understanding the escape mechanism of Candida albicans, it is possible to developed antifungal or Candida vaccine in the future, therefore the incidence of candidiasis can be suppressed.